PENGARUH KECERDASAN INTELEKTUAL, EMOSIONAL, DAN SPIRITUAL TERHADAP PEMAHAMAN AKUNTANSI - MUHAMMAD DAUD MAHMUD (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study aims to examining the effects of intellectual, emotional, and spiritual intelligence on students' understanding of accounting both partially and simultaneously. The objects of this study are 58 final-year students who have taken 136 of academic credits (SKS) and passed the compulsory courses in Accounting Program at the Faculty of Economics, Universitas Muhammadiyah Maluku Utara. This study used quantitative methodology with multiple linear regression as an analysis tool. The data used consists of primary and secondary data. The primary data on this sudy were tabulation results of respondent’s answers obtained through questionnaires, while secondary data were obtained from student’s scores in the Accounting Program’s archives at the Faculty of Economics, Universitas Muhammadiyah Maluku Utara. The results of this study are as follows. (1) The intellectual intelligence and spiritual intelligence do not have any influence in students' understanding of accounting partially while emotional intelligence does. (2) Those three intelligences do not effect the students' understanding of accounting by simultaneously.